Parīkṣāmukhaṃ - Māṇikyanandī, 8th cent (SAMP early 20th-century Indian books project, 1940)
Classical commentary on Parīkṣamukham of Mānikyanandī, 8th cent., treatise on Indian logic (Nyaya), according to the Jaina Digambara sect.